2011
DOI: 10.1007/s00420-010-0608-1
|View full text |Cite
|
Sign up to set email alerts
|

Stage fright: its experience as a problem and coping with it

Abstract: Stage fright was experienced as a problem and perceived as having negative career consequences by a considerable percentage of the surveyed students. In addition to a desire for more help and support, the students expressed an openness and willingness to seriously discuss and address the topic of stage fright. This provides a necessary and promising basis for optimal career preparation and, hence, an opportunity to prevent occupational problems in professional musicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 21 publications
3
49
1
3
Order By: Relevance
“…The CG showed values of 44.00 (SD = 10.85) in the pretest and 44.25 (SD = 14.40) in the posttest. The values showed no significant differences to the norm value of music students (Studer et al, 2011) whereas the participants in the IG indicated a slight tendency of a lower STAI-S value in the posttest compared to the norm sample (t(12) = 1.92; p = 0.07). The analysis between the two measuring points showed a significant interaction effect of time and group (F(1,19) = 5.93, p = 0.02).…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…The CG showed values of 44.00 (SD = 10.85) in the pretest and 44.25 (SD = 14.40) in the posttest. The values showed no significant differences to the norm value of music students (Studer et al, 2011) whereas the participants in the IG indicated a slight tendency of a lower STAI-S value in the posttest compared to the norm sample (t(12) = 1.92; p = 0.07). The analysis between the two measuring points showed a significant interaction effect of time and group (F(1,19) = 5.93, p = 0.02).…”
Section: Resultscontrasting
confidence: 52%
“…The mean values of a representative sample of university students are for the STAI-T 41.14 (SD = 8.68, n = 393) and for the STAI-S 41.42 (SD = 10.13, n = 393, Laux et al, 1981). In a sample with music students, Studer et al (2011) found the average value of the STAI-S to be 47.00 (SD = 11.00, n = 190). In our sample, the STAI-T values did not differ significantly from the norm sample (t(20) < 1.0).…”
Section: Measuring Instrumentsmentioning
confidence: 97%
“…We were able to show that there is only a moderate association between the degree of anxiety experienced and the degree to which stage fright is perceived as a problem (22). Furthermore, no study has yet investigated the association between hyperventilation complaints and the experience of stage fright as a problem.…”
Section: Introductionmentioning
confidence: 72%
“…3,5,8 In a literature review, Brugué s 9 found rates ranging from 16 to 70% in survey-type studies carried out with orchestra musicians in the 1980s and 1990s in the United States and European countries. Other studies, such as those of Steptoe, 10 Ryan & Andrews, 5 and Studer et al, 11 confirm this panorama, with variable but mostly high rates of MPA.…”
Section: Introductionmentioning
confidence: 76%